Conservative Treatment of an Intra-Articular Shear Fracture of the Ulnar Head - Miyamoto, Hideaki; Sasaki, Gen; Kurozumi, Taketo; Watanabe, Yoshinobu (Journal of Wrist Surgery, 2019)
Background Isolated intra-articular fracture of the ulnar head is rare.Case Description A 59-year-old woman experienced an ulnar head fracture involving the distal radioulnar joint after a fall at ground level. The intra-articular fragment of the ulnar head was rotated into anatomical alignment with an above-elbow cast in 90° of supination for 4 weeks. A below-elbow night splint was retained for 2 additional weeks. Twelve months post-injury, full active motion and bone union were achieved.Literature Review Only three studies have reported treatment of isolated intra-articular ulnar head fractures, and in all cases open reduction and internal fixation were performed.Clinical Relevance Our report demonstrated good results for the conservative treatment of an intra-articular ulnar head shear fracture, with early recovery of forearm rotation and wrist function.
Keywords: conservative treatment; intra-articular fracture; shear fracture; ulnar head fracture